Platelet-rich fibrin or platelet-rich plasma - which one is better? an opinion - Shweta Bansal; Arun Garg; Richa Khurana; Parul Chhabra (Wolters Kluwer Medknow Publications, 2017)
The healing of hard and soft tissue in mediated by a wide range of intracellular and extracellular events that are regulated by signaling proteins. Platelets can play a crucial role in periodontal regeneration as they are the reservoirs of growth factors and cytokines which are the key factors for regeneration of bone and maturation of soft tissue. Platelet-rich plasma (PRP) is first generation platelet concentrate. However, the short duration of cytokine release and its poor mechanical properties have resulted in search of new material. Platelet-rich fibrin (PRF) is a natural fibrin-based biomaterial prepared from an anticoagulant-free blood harvest without any artificial biochemical modification (no bovine thrombin is required) that allows obtaining fibrin membranes enriched with platelets and growth factors. The slow polymerization during centrifugation, fibrin-based structure, ease of preparation, minimal expense makes PRF somewhat superior in some aspect to PRP.